(untitled) (Research, Society and Development, 2022)
The present work evaluated the biotechnological potential of the fungus Penicillium sclerotiorum UCP 1040, isolated from the soil of the State of Pernambuco, for the production of biosurfactant using agro-industrial waste as alternative sources of carbon and nitrogen. Fermentations were carried out for 144 h, 28ºC and 150 rpm, in media consisting of different concentrations of post-frying oil (PFO) and corn steep liquor (CSL), according to a 22 factorial design. The effects of substrates on surfactant production were evaluated through statistical analysis, using surface tension as response variable. The emulsifying and dispersing properties of biosurfactant were investigated by emulsification index (EI24) and dispersion test, respectively. The results obtained showed that P. sclerotiorum was able to produce a surfactant compound in the presence of renewable substrates, with the greatest reduction in surface tension (from 72.0 to 42.77 mN/m) in condition 2 of the design (medium consisting of 3% PFO and 5% CSL). Although the biosurfactant produced in this condition did not show good emulsifying properties, it exhibited excellent dispersing properties, with oil dispersion area (ODA) of 44.18 cm2. The Pareto diagram verified the significant influence of the interaction of wastes in the production of biosurfactant, constituting alternative and low-cost substrates, which make the bioprocess economical and, therefore, attractive for different industries.